Evidence for centennial‐scale Lateglacial and early Holocene climatic complexity from Quoyloo Meadow, Orkney, Scotland. (22nd February 2021) - Timms, Rhys G. O.; Abrook, Ashley M.; Matthews, Ian P.; Francis, Christopher P.; Mroczkowska, Agnieszka; Candy, Ian; Brooks, Stephen J.; Milner, Alice M.; Palmer, Adrian P.
Abstract: The influence of the North Atlantic on the margins of Europe means the region is particularly sensitive to changes in the ocean–atmospheric system. During the Last Glacial–Interglacial Transition (16–8 cal ka bp ) this system was repeatedly disrupted, leading to a series of abrupt and short‐lived shifts in climate. Despite much research, the number and magnitude of these 'centennial‐scale' events is not well understood. To address this, we expand upon investigations at Quoyloo Meadow, Orkney, Scotland, one of the best chronologically constrained palaeoclimate records in northern Britain. By coupling stable isotope and chironomid fossil analyses with existing data, this study identifies multiple phases of centennial‐scale disturbance at: c . 14.0, 11.1, 10.8, 10.5, 10.45 and 10.3 cal ka bp, with the events at 14.0 and 10.3 exhibiting a particularly pronounced cold‐climate signature. During the Holocene, the strongest response to climate forcing was at c . 10.3–10.0 cal ka bp, expressed as a two‐stage drop in mean July temperatures, a shift in pollen spectra indicative of 'less‐stable' climatic regimes, and a depletion in δ 18 O values. We interpret this as the first reliably dated incidence of the '10.3‐ka event' in the British Isles and consider the wider impact of this climatic reversal in other Holocene records.